2022
DOI: 10.1097/meg.0000000000002411
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab versus ustekinumab as first-line biological in moderate-to-severe Crohn’s disease: real-life cohort from a tertiary referral center

Abstract: Background Therapeutic options for Crohn’s disease are growing, making the choice of first-line therapy relevant. Both adalimumab and ustekinumab are effective in moderate-to-severe Crohn’s disease. The Safety and Efficacy of Adalimumab Versus Ustekinumab for One Year trial suggested no difference in clinical or endoscopic remission at week 52 in biological-naive Crohn’s disease patients. We explored if results withstand in the real world. Methods We included bio-naive Crohn’s disease patients starting adali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Among the 63 publications, 10‐72 58 were journal articles and 5 were international conference abstracts. Two conference abstracts 71,72 were replaced by subsequent published articles found in our search.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 63 publications, 10‐72 58 were journal articles and 5 were international conference abstracts. Two conference abstracts 71,72 were replaced by subsequent published articles found in our search.…”
Section: Resultsmentioning
confidence: 99%
“…Zhdanava et al reported that, at 12 months, bio-naïve UST-treated CD patients showed a significantly higher treatment persistence rate than ADA-treated CD patients [ 85 ]. On the other hand, a Belgian study was unable to detect differences in the clinical remission rate between ADA and UST bio-naïve CD patients at week 26 (adjusted odd ratio [aOR] 1.30; p = 0.72) and at week 52 (aOR, 1.60; p = 0.41) [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other treatments are usually recommended for refractory patients or those with specific contraindications to anti-TNF-α drugs [ 108 ]. The real-life data for the use of UST in this setting are still scarce and limited by small sample sizes and large heterogeneity of therapy protocols/outcome definitions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 35 , 45 , 47 , 48 , 55 , 61 , 62 , 63 , 68 , 69 , 70 , 71 , 72 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , …”
Section: Resultsmentioning
confidence: 99%
“…Moens et al [ 13 ] reported no significant difference between the two groups in terms of adverse events (24 in each group) within the first year of treatment. No serious infections were reported nor were any death reported in any of the two groups.…”
Section: Reviewmentioning
confidence: 99%
“…The most common adverse event reported by Sands et al [ 14 ] was infection in 34% and 41% of the ustekinumab and adalimumab groups respectively. Moens et al [ 13 ] reported that in any eight events of infections in ustekinumab and 10 events of infections in adalimumab groups.…”
Section: Reviewmentioning
confidence: 99%